2012
DOI: 10.1007/s00406-012-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of 403 patients with mood disorders 48 to 52 years after their psychiatric hospitalisation

Abstract: The purpose is to analyse differences in mortality among patients with major depressive disorders (MDD), bipolar-II (BP-II), bipolar-I (BP-I) disorders and mania with or without minor depressive disorders and to identify risk factors of mortality. The sample represents all admissions for depression or mania over 5 years (1959-1963) to the Psychiatric Hospital of Zurich University, serving a large area. 403 patients were included and followed up every 5 years until 1985; thereafter, mortality data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 38 publications
2
26
1
1
Order By: Relevance
“…There is a discrepancy between our study which showed no evidence of increased risk of myocardial infarction in BD and the relatively higher mortality rate of myocardial infarction in BD, in comparison to the general population (3, 44, 78). We postulate three possible explanations: i) patients with BD and the general population have similar rates of MI, but the lethality is greater in BD; this is supported by data reporting higher mortality rates of patients with severe mental illness (including BD) after admission due to acute heart disease (43); ii) patients with BD receive less medical care for MI than general population, either because they have poor access to health care (17) or lower rates of cardiovascular health care utilization and invasive cardiac diagnostic/therapeutic procedures (43); iii) patients with BD may be at higher risk of post-MI arrhythmias and sudden cardiac death (58) out of the hospital, which may underestimate the true risk of myocardial infarction.…”
Section: Discussioncontrasting
confidence: 94%
“…There is a discrepancy between our study which showed no evidence of increased risk of myocardial infarction in BD and the relatively higher mortality rate of myocardial infarction in BD, in comparison to the general population (3, 44, 78). We postulate three possible explanations: i) patients with BD and the general population have similar rates of MI, but the lethality is greater in BD; this is supported by data reporting higher mortality rates of patients with severe mental illness (including BD) after admission due to acute heart disease (43); ii) patients with BD receive less medical care for MI than general population, either because they have poor access to health care (17) or lower rates of cardiovascular health care utilization and invasive cardiac diagnostic/therapeutic procedures (43); iii) patients with BD may be at higher risk of post-MI arrhythmias and sudden cardiac death (58) out of the hospital, which may underestimate the true risk of myocardial infarction.…”
Section: Discussioncontrasting
confidence: 94%
“…The development of these scales is also essential in order to detect high-risk individuals as soon as possible so that intervention is not delayed and the likelihood that patients will receive appropriate treatment and therapeutic care is increased [3,4]. Such an approach is particularly relevant in the case of bipolar disorder (BD I and II), which is a cause of premature death and leads to a significant impairment of both social and cognitive functioning [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the Zurich cohort of initially hospitalized patients, roughly 15% of individuals with major depressive disorder had committed suicide after 50 years [1]. Over the same period of time, the risk of completed suicide in a Swedish community sample of patients with depression averaged approximately 6%, whereas the risk amounted to 14% in the subgroup of patients with severe major depressive disorder [2].…”
Section: Introductionmentioning
confidence: 99%